ANALISIS BREAK EVEN POINT (BEP) dan EFISIENSI EKONOMI PENGGUNAAN DAUN SALVINIA MOLESTA PADA AYAM BROILER BETINA - Eka Septiadi; Agus Setiadi; Migie Handayani (MEDIAGRO, 2017)
This study aims to determine the performance of broiler females that were given extra rations Salvinia molesta, to analyze the BEP and the economic efficiency of the use of leaves of Salvinia molesta in broiler chickens females were given rations of leaves Salvinia molesta, and to determine the economic efficiency of the use of leaves of Salvinia molesta in the ration of broiler chickens female. The research material using the 100 head of DOC strain females age 2 weeks. The method used is the method of completely randomized design (CRD), the research done by 4 treatments and 5 replications. The treatments were differences in the provision of the proportion of Salvinia molesta in feed, namely T0 = no additional Salvinia into feed, T1 = 6% increase Salvinia in feed, T2 = 12% addition of Salvinia in feed, T3 = 18% addition of Salvinia in feed. The results showed consumption was not significantly different (P> 0.05), while the United Nations and the FCR were significantly different (P <0.05). Break even point of the lowest of live chickens at T0 by 22 tails generate USD. 646 138, 00 and the break even point T0 carcass by 8 tail generate USD. 285,959.00. The most economical high efficiency T1 with efficiency 1.085 / 25 animals live sale, and 1,447 / 25 animals for sale carcass. Keywords: Broilers females, Salvinia molesta, Break even point, Economic efficiency